Systematics and Phylogeography of "Carex capitata" Complex (Cyperaceae) - Villaverde Hidalgo, Tamara M. (Université d'Ottawa / University of Ottawa, 2012)
Only thirty known species have populations at high latitudes in both hemispheres, this is, a bipolar distribution. Five of them belong to the genus Carex. Before attempting to elucidate the origins of such distributions, we need to resolve taxonomical problems that are typically encountered in such species. We focus on the Carex capitata complex, which includes Carex arctogena as a bipolar species, in worldwide scope sampling. A morphometric study and phylogenetic analyses based on maximum parsimony, Bayesian inference and Statistical Parsimony have revealed: a) C. capitata and C. arctogena are different species; b) C. anctarctogena is a synonym of C. arctogena and c) a great biodiversity previously undetected in western North America that could lead to the description of three new taxa (“Carex cayouetteana”, Carex sp. nov. 1 and 2) comprised in the so called “C. cayouetteana” lineage. More studies are needed in some C. capitata samples from Russia that appears in the molecular analyses in a strongly supported clade.
Keywords: Carex; Cyperaceae; Taxonomy; Systematics; Phylogeography; Bipolar disjunction